Religious Moderation in the Practice of Interfaith Marriage: A Case Study of Silvia Tan and Ko Muadz - Fathiyah, Husna; Arisandi, Bustomi; Mudarris, Mudarris (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
This study explores religious moderation in the context of interfaith marriage in Indonesia through the case of Shilvia Tan (Muslim) and Ko Muadz (Confucian), who have lived harmoniously for 17 years without religious conversion. The purpose is to analyze how religious moderation is practiced in interfaith households and how this case reflects tensions between state law, religious doctrine, and individual rights. The originality of this research lies in its interdisciplinary perspective that combines legal, religious, and sociological analysis with the lived experience of an interfaith couple, filling a gap in previous studies that largely focused on normative or legal aspects.Using a qualitative approach, the study employs literature review and media analysis of academic works, legal documents, news reports, and social media discussions from 2007 to 2024. Data were thematically analyzed to identify issues such as legal challenges, public perceptions, and representations of religious moderation.Findings show that interfaith marriage reveals structural obstacles in legal recognition and highlights the gap between the state’s discourse of moderation and the lived realities of citizens. The case demonstrates that tolerance and family harmony can be achieved without conversion, but more inclusive legal and social policies are needed to address the needs of Indonesia’s plural society